2020
DOI: 10.31557/apjcc.2020.5.1.27-32
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Nigeria: A Tertiary Hospital Experience

Abstract: Background: Cancer is a poorly addressed major cause of morbidity and mortality in Nigeria.Aim: The study aims at analyzing the age, gender and topography of cancer in Delta State, Nigeria.Setting: The research was conducted in the State tertiary health care center, the major referral center in Delta State, Nigeria.Materials and Methods: This is a 6-year (2014-2019) descriptive retrospective study of all histologically diagnosed cancer cases in the department of Histopathology, DELSUTH.Results: Cancer accounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
3
11
2
Order By: Relevance
“…Similarly, in an earlier report from the Benin Cancer Registry, located in the South Senatorial District of this state (not covered by the current study), Obaseki et al found a ratio of 1:1.5 [16]. This high preponderance of cancers in females seen in this state is consistent with findings from many states in Nigeria [8,13,[17][18][19][20][21]. The bias for the female gender can be attributed to high proportion of female breast cancer and cervical cancer among the common cancer types seen in the country.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similarly, in an earlier report from the Benin Cancer Registry, located in the South Senatorial District of this state (not covered by the current study), Obaseki et al found a ratio of 1:1.5 [16]. This high preponderance of cancers in females seen in this state is consistent with findings from many states in Nigeria [8,13,[17][18][19][20][21]. The bias for the female gender can be attributed to high proportion of female breast cancer and cervical cancer among the common cancer types seen in the country.…”
Section: Discussionsupporting
confidence: 90%
“…In males, this study observed prostate cancer, colorectal cancer, NMSC, NHL, and bone and soft tissue cancer as the 5 most common cancers in this part of Edo State, Nigeria. But for the order of ranking, the cancers were also the top 5 documented by Uchendu OJ in Delta State while bladder cancer displaced NHL from the list of top 5 male cancers in Kano State [13,17]. In the earlier report in this state by Obaseki et al, bladder and oesophageal cancers replaced NHL, and bone and soft tissue cancer among the top 5 most frequently diagnosed cancers in this study.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Individually, apart from prostate cancer, most cancer peaked right from the 60-64 years age group in this study. Earlier studies had shown that most cancers peaked much earlier than the age of 60 years [27]. The implication for policy makers and legislators is that planning of cancer prevention through public enlightenment on behavioral changes and risk factor modification, cancer screening and vaccination, should target much younger age groups as carcinogenesis is a multi-step evolving process that Carcinoma is the most common geriatric malignancy in this study, accounting for 94.7% of the cancer.…”
Section: Discussionmentioning
confidence: 61%